Elevation of AST/ALT Ratio in Association with Severity of Esophageal Varices in Patients with Hepatic Cirrhosis - Imran Khan, Mukhtar Ahmad, Fahad Aman Khan, Muhammad Kashif, Tashia Malik, Aniqa Anser Tufail Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the elevation of AST/ALT ratio in association with severity of esophageal varices in patients with hepatic cirrhosis. Study Design: Cross sectional survey Place and Duration of Study: Medical Unit II, Jinnah Hospital Lahore from November 2018 to April 2019 Methodology: One hundred and ten subjects were enrolled. The complete history, physical examination and appropriate investigations were done like liver functions test to see the ratio of AST/ALT and upper GI Endoscopy to confirm the presence or absence of esophageal varices. Results: The mean age of the patients was 45.6±5.2 years with 77.27% males and 22.73% females. Paquet grading system showed that esophageal varices were presented in 20.9% grade II. Within the 65 cases of esophageal varices 30 patients of liver cirrhosis were having a 27% high risk of esophageal varices. ALT and AST were significantly higher in high risk esophageal varices. Conclusion: The elevated level of ALT and AST are significantly associated with the severity of esophageal varices in hepatic cirrhosispatients.